Pengaruh Dukungan Organisasi dan Employee Engagement terhadap Kinerja Pegawai pada Badan Kepegawaian Daerah Kabupaten Sidoarjo - Denta Umihastanti; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study discusses the analysis of the influence of organizational support and employee engagement on civil servant performance at a regional civil service agency. This study uses a quantitative research method by distributing questionnaires to all civil servants of a regional civil service agency as many as 59 employees using a Likert scale from numbers one to five. The data analysis technique used in this study is multiple linear regression analysis with data quality testing carried out through validity and reliability tests using SPSS version 20. This study shows that organizational support has a significant effect on the positive and significant impact on employee performance, which means that the higher the support provided, the higher the performance of an employee. The study results also show that employee engagement positively and significantly affects employee performance. The higher the employee's sense of attachment to his work, the higher the quality of his performance at work. Furthermore, the test results also prove that organizational support and employee engagement positively influence civil servant performance at a regional civil service agency. This research is expected to be used by the regional civil service agency to increase organizational support, such as giving awards in verbal praise as an appreciation of employee achievements at work so that later they can improve performance to achieve organizational goals.